Bonding strength between a hard chairside reline resin and a denture base material as influenced by surface treatment - Leles, C. R.; Machado, Ana Lucia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Giampaolo, E. T.; Pavarina, Ana Claudia [UNESP] (Blackwell Publishing, 2001)
Direct relining of dentures made with hard chairside reline resins is faster than laboratory-processed reline systems and the patient is not without the prosthesis for the time necessary to perform the laboratory procedures. However, a weak bond between the autopolymerizing acrylic reline resins and the denture base material has been observed. This study evaluated the effect of six different surface treatments on the bond strength between a hard chairside reline acrylic resin and ia heat-cured acrylic resin. Specimens of the heat-cured acrylic resin were divided into seven groups. one of these groups remained intact. In the other groups, a 10-mm square section was removed from the centre of each specimen. The bonding surfaces were then treated with (i) methyl methacrylate monomer, (ii) isobutyl methacrylate monomer, (iii) chloroform, (iv) acetone, (v) experimental adhesive and (vi) no surface treatment-control group. Kooliner acrylic resin was packed,into the square sections and polymerized. The bonding strength was evaluated by a three-point loading test. The results were submitted to one-way analysis of variance (ANOVA) followed by a Tukey multiple range test at a 5% level of significance. No significant difference was found between the surface treatment with Lucitone 550 monomer or chloroform, but both were stronger than the majority of the other groups. The bond strength provided by all the surface treatments was lower than that of the intact heat-cured resin.
Keywords: reline resin; bond strength; denture base resin; removable prosthodontics